Connecting curricula content with career context: the value of engineering industry site visits to students, academics and industry. (1st November 2020) - Carbone, Angela; Rayner, Gerry M.; Ye, Jing; Durandet, Yvonne
ABSTRACT: Work-integrated learning (WIL) has become an increasingly conspicuous and valued component of student learning at university. Given the limits to scale for WIL-related internships and placements, other forms of WIL, such as field trips and site visits, have become more common in undergraduate engineering curricula. However, these forms of WIL are under-researched in terms of their value to the various stakeholders. This study invited undergraduate engineering students from an Australian university, who participated in site visits at two leading Engineering organisations, to provide feedback on their experience. Unsolicited feedback was also provided by academic staff. The results highlight the range of values and impacts of a WIL site visit programme on students, academics, industry partners and to engineering curricula. These include refining and expanding students' perceptions of their career work and identity, a strengthening of university-industry collaborations, and a reshaping of engineering curricula based on student and industry partner feedback.